The Importance of Subjective Well-Being and Character Strength for Equality Education at the Prison - Moh Fikri Tanzil Mutaqin; Laksmi Evasufi Widi Fajari (International Journal of Asian Education, 2022)
The phenomena that occur in prisoners are very complex such as loss of life satisfaction, hope, and independence, and they have limitations in social interaction. In addition, other phenomena often occur in prisoners, namely the dropping out of school because they have to undergo a period of detention (Kintamani, 2012). While in the socialization institution, they still get the right to enjoy proper education through equality education. As citizens learning equality education, they can also not be separated from the problems that prisoners often experience. Seeing this phenomenon, the author assumes that learning about citizens is important for subjective well-being and character strength. When citizens learn to have subjective well-being and character strength, they can have life productivity (Holder, 2012). This article is discussed using the literature review method by conceptualizing the grand theory and the results of previous research on subjective well-being and the strength of character combined in the learning process of equality education in social institutions. The purpose of this paper is to support research literature exploration of subjective well-being and exploration of character education